Rekomendasi Handheld Gaming PC Menggunakan MEREC untuk Pembobotan Objektif dan MARCOS untuk Pemeringkatan - Sanriomi Sintaro; Sandi Badiwibowo Atim (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2026)
This study proposes a decision support system to select a handheld gaming PC by integrating the MEREC weighting method with the MARCOS ranking method. Sixteen devices were evaluated using Tokopedia price data and technical specifications across nine criteria: price, SSD capacity, RAM capacity, battery capacity, device weight, screen size, refresh rate, total screen pixels, and a display-type score (OLED=3, IPS=2, LCD=1). MEREC indicates SSD capacity is the most influential criterion (wC2=0.2085), followed by total pixels (wC8=0.1497) and display score (wC9=0.1389). MARCOS ranks MSI CLAW 8 first with Si=0.7652 and f(Ki)=0.6776, followed by ROG Xbox Ally X Premium and ASUS ROG Ally X (both Si=0.7535; f(Ki)=0.6672). The results show that storage and display attributes dominate recommendations for the observed dataset, and the framework provides an explainable, data-driven ranking that can be updated when market prices change.